Peningkatan Literasi Keuangan dan Teknologi Keuangan Terhadap Masyarakat Pedesaan - Utami, Novia; Kusumahadi, Teresia Angelia (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Kelor Village in Gunungkidul Regency, Yogyakarta, is an agrarian village where the majority of the population works as farmers. However, the low level of education in this village has led to very limited financial literacy among the community. This issue is crucial because many villagers struggle to manage their income from agriculture, making it difficult for them to budget, save, or invest wisely. As a result, the economic well-being of the community has not significantly improved. Additionally, limited access to formal financial institutions forces many residents to keep their money at home, which poses a risk. To address this problem, enhancing financial literacy and promoting the use of financial technology (fintech) are necessary. This training aims to provide better understanding of financial literacy and encourage the use of fintech among the people of Kelor Village. Although some community members already have a basic understanding of financial literacy, many do not regularly record their finances and lack a full grasp of the concepts and benefits of fintech. The educational program implemented has successfully improved the community’s understanding; however, the implementation in daily life still needs reinforcement. The results of this program show that those who received education are better at managing their finances and more open to using financial technology. Therefore, it is recommended to expand the educational program with more easily understood and relevant materials, as well as providing practical training to encourage the use of financial technology. Additionally, improving access to formal financial services and empowering community groups are crucial to ensuring the sustainability of the program. Through this approach, the people of Kelor Village are expected to be better prepared to face economic uncertainties and improve their financial well-being.